(untitled) (Acta Scientiarum. Agronomy, 2010)
Competition experiments were installed at the COODETEC unit in Palotina, Paraná State, with the objective of evaluating the influence of the cultivation of soybean in succession to a second crop season on different sowing dates on the agronomic traits and seed yield in both cultures. The experiment consisted of four field replicates, arranged in a completely randomized block design and carried out in two agricultural years (2003/2004 and 2004/2005). The individual blocks were comprised of three early-maturing soybean cultivars (CD 202, CD 215 and CD 216) sowed on five different dates (9/15, 9/30, 10/15, 10/30 and 11/15) and also three corn hybrids (CD 305, CD 306 and CD 308) that were sowed on different dates (1/30, 2/15, 3/1, 3/15 and 3/30). Data were submitted to a joint analysis, and the interaction decompositions were made when verified significance. Based on the results obtained, it can be concluded that early season second crop growing is a valid strategy for obtaining a good agronomical performance and better productivity in off-season corn sowing. The succession of early soybean/early corn in the off-season is a potentially viable alternative for the west region of Paraná State, as long as the soybean sowing is done by the first half of October and the second crop season corn is sown in the first half of February.